Hydrolysis and Hydrazinolysis of Isatin-Based Ald- and Ketazines - Hany S. Ibrahim; Soha R. Abdelhadi; Hatem A. Abdel-Aziz (Journal of Chemistry)
The hydrolysis of isatin aldazine 4a–d afforded the unexpected 3,3′-(hydrazine-1,2-diylidene)bis(indolin-2-one) (5) and 1,2-di(arylidene)hydrazines 6a–d through dual hydrolysis of 4a–d. A mechanism to explain the formation of 5 and 6a–d was proposed. In addition, the hydrazinolysis of 4a–d yielded 3-hydrazonoindolin-2-one (2) and 1,2-di(arylidene)hydrazines 6a–d instead of hydrazones 17a–d, while hydrazinolysis of isatin ketazine 5 gave the expected 3-hydrazonoindolin-2-one (2). These results indicated the ability of the title compounds for unusual hydrolysis and hydrazinolysis reactions.